“La fiesta de los reyes de Licán y su incidencia en los habitantes de la parroquia de Licán comprendidos de 28 a 40 años, en el período de enero 2005 a enero 2016” - Estrella Escudero, Evelyn Erica (2017)
The research project: “THE FESTIVITY “REYES FROM LICÁN” AND ITS INCIDENCE ON THE 28-40 YEARS OLD-INHABITANTS OF LICAN COUNTY DURING THE PERIOD JANUARY 2005 – JANUARY 2016” had the purpose to carry out a coherent analysis of the incidence of the festivity Los Reyes on a group of inhabitants of Lican County, Riobamba Canton and the level of identity of these population with this festivity, do that a contribution to the conservation of the tradition can be made. Communication tools such as: surveys, interviews and observation cards were used. Nowadays, the festivity is considered a place where the maximum expression is evident in the characters and activities which are part of the tradition. They, in a great way, have changed their own tradition as the years pass. For this reason, this research is bases on the scientific method which is ideal for this procedure. It used two methodologies: Inductive – deductive and analytic – synthetic. The Reyes festivity does affect the selected group, and they have made the party to become bigger, however somme details have disappeared over the time. Therefore, it is importanta that the new generations take part on the conservation of this tradition not only in the country but also out of its borders by creating strategies to keep the festivity alive during the whole year.